Pemahaman dan Preferensi Konsumen terhadap Produk dan Layanan Keuangan Syariah di Era Digital - Dimaz Agung Bhagas; Triana Dian Permata; Uswatun Hasanah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the influence of effectiveness, efficiency, and financial literacy in the use of QRIS on financial inclusion among Generation Z in Bengkulu City. The data was obtained from questionnaires distributed to Generation Z aged 20-24 years in Bengkulu City who had used QRIS. The sample was taken using purposive sampling. This study used a quantitative method with descriptive statistical analysis, validity test, reliability test, classical assumption test, linearity test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the variables of efficiency and financial literacy have a significant relationship with financial inclusion, while the variable of effectiveness does not have a significant effect on financial inclusion among Generation Z in Bengkulu City. Keywords: Effectiveness; Efficiency; Financial Literacy; QRIS; Financial Inclusion